Conflict in forest management: a study for collaborative forest management in Indonesia - Yasmi, Yurdi (Wageningen University & Research, 2002)
The main objective of the study was to obtain a better understanding of forestry conflicts, particularly in the context of the Bulungan Research Forest (BRF) in East Kalimantan. The results show that conflict took place between local people within a particular locality (settlement); between different localities; and between local people and various companies (e.g. logging, coal-mining) operating near their localities. In term of conflict resolution, the people from the communities have proposed three kinds of mechanisms for different types of conflicts. Those mechanisms are adat (customary laws), government involvement and negotiation. The key task one faces in undertaking conflict resolution is to manage its occurrence. The overall goal should not be to eliminate conflict; instead, it should be to adopt procedures or mechanisms for maximizing its potential benefits while minimizing its potential drawbacks. This study concludes that choosing the “best” conflict resolution mechanism is, in itself, a strategic choice. There is no single panacea for resolving any kind of conflict situation.